Influence of Nanobubble Size Distribution on Ultrasound-Mediated Plasmid DNA and Messenger RNA Gene Delivery - Kida, Hiroshi; Feril, Loreto B.; Irie, Yutaka; Endo, Hitomi; Itaka, Keiji; Tachibana, Katsuro (Frontiers in Pharmacology, 2022)
The use of nanobubbles (NBs) for ultrasound-mediated gene therapy has recently attracted much attention. However, few studies have evaluated the effect of different NB size distribution to the efficiency of gene delivery into cells. In this study, various size of albumin stabilized sub-micron bubbles were examined in an in vitro ultrasound (1 MHz) irradiation setup in the aim to compare and optimize gene transfer efficiency. Results with pDNA showed that gene transfer efficiency in the presence of NB size of 254.7 ± 3.8 nm was 2.5 fold greater than those with 187.3 ± 4.8 nm. Similarly, carrier-free mRNA transfer efficiency increased in the same conditions. It is suggested that NB size greater than 200 nm contributed more to the delivery of genes into the cytoplasm with ultrasound. Although further experiments are needed to understand the underlying mechanism for this phenomenon, the present results offer valuable information in optimizing of NB for future ultrasound-mediate gene therapy.